Temporal alterations of the nascent proteome in response to mitochondrial stress - Tomasz M. Stępkowski; Vanessa Linke; Dorota Stadnik; Maciej Zakrzewski; Anna E. Zawada; Remigiusz A. Serwa; Agnieszka Chacinska (Cell Reports, 2024)
Summary: Under stress, protein synthesis is attenuated to preserve energy and mitigate challenges to protein homeostasis. Here, we describe, with high temporal resolution, the dynamic landscape of changes in the abundance of proteins synthesized upon stress from transient mitochondrial inner membrane depolarization. This nascent proteome was altered when global translation was attenuated by stress and began to normalize as translation was recovering. This transition was associated with a transient desynchronization of cytosolic and mitochondrial translation and recovery of cytosolic and mitochondrial ribosomal proteins. Further, the elongation factor EEF1A1 was downregulated upon mitochondrial stress, and its silencing mimicked the stress-induced nascent proteome remodeling, including alterations in the nascent respiratory chain proteins. Unexpectedly, the stress-induced alterations in the nascent proteome were independent of physiological protein abundance and turnover. In summary, we provide insights into the physiological and pathological consequences of mitochondrial function and dysfunction.